Kunxinning granules alleviate perimenopausal syndrome by supplementing estrogen deficiency - Wang, Wenshuang; Yang, Wen; Wang, Fangwenting; Gao, He; Liu, Kaixin; Zhang, Jinling; Li, Yunjuan; Zhang, Man; Zhou, Guirong; Hou, Yuanyuan; Bai, Gang (Frontiers in Pharmacology, 2025)
IntroductionOvarian function decline results in reduced estrogen levels, leading to endocrine disorders, oxidative stress damage, and excessive activation of inflammatory factors, all of which contribute to the development of premenstrual syndrome (PMS). Kunxinning Granules (KXN) has been clinically approved for PMS treatment, but its bioactive ingredients and mechanism of action remain unclear. This study aimed to investigate the active metabolites and molecular mechanism of KXN in treating PMS rats, laying a foundation for the clinical development of PMS treatment.MethodsAn ovariectomized (OVX) rat model was established to evaluate the efficacy of KXN in treating PMS. Molecular network (MN) analysis, combined with UPLC/Q-TOF-MS, identified prototype compounds in the samples and constructed a chemical classification map based on their structures. A network analysis and proteomics were conducted to predict potential pathways through which KXN regulates PMS. Quantitative metabolomics assays were used to confirm these potential pathways. Additionally, target prediction and binding enzyme activity detection elucidated the key active metabolites and mechanisms of action in KXN.ResultsKXN exhibited significant effectiveness in supplementing estrogen deficiency and uterine atrophy in the OVX model. We identified 16 absorbed metabolites as the potential pharmacological ingredients of KXN in vivo. The steroid hormone biosynthesis pathway, a crucial pathway of KXN in PMS, played a key role in KXN’s effectiveness. KXN improved hormonal metabolic disorders by regulating this pathway. The main metabolites in KXN, including astragaloside IV, icariin and baohuoside I increased estradiol levels by enhancing the activity of CYP19A1, the representative enzyme in hormone biosynthesis pathway.DiscussionThis study shows that KXN could relieve anxiety, depression, and osteoporosis in PMS. This pharmacological effect is exerted through steroid hormone synthesis to address estrogen deficiency. The findings provide valuable insights into the underlying mechanisms and support its clinical application.